Tradisi intelektual NU : Lajnah Bahtsul Masa'il, 1926-1999 - Zahro, Ahmad, 1955- (Yogyakarta : LKiS, 2004)
Study of the development of Lajnah Bahtsul Masa'il, an Islamic research center of the Nahdlatul Ulama, 1926-1999, in Indonesia
Revision of the author's thesis (doctoral)--Institut Agama Islam Negeri Sunan Kalijaga
Includes bibliographical references (p. [273]-289) and index
Keywords: Nahdhatul Ulama; Political parties -- Indonesia; Islam -- Indonesia; Nahdlatul Ulama; -- Islam; -- Indonesia